2015
DOI: 10.1007/s10695-015-0138-6
|View full text |Cite
|
Sign up to set email alerts
|

Establishment from the snout and kidney of goldfish, Carassius auratus, of two new cell lines and their susceptibility to infectious pancreatic necrosis virus

Abstract: Goldfish Carassius auratus are commonly used in scientific research and have a significant economic value in the pet trade. In this study, two cell lines were established from the snout and kidney tissue of goldfish, in order to create a biological monitoring tool for viral diseases. Cell lines were optimally maintained at 25 °C in M199 medium supplemented with 15-20 % fetal bovine serum. Chromosomal analysis indicated that both cell lines remained diploid, with a mean chromosomal count of 100. Results of vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…KB cells are well adapted to growth at 27°C in L-15 supplemented with 10% FBS without CO 2 . Many cell lines derived from fish are known to grow best between 25 and 30°C (Goswami, Sharma, Bahuguna, Nagpure, & Lakra, 2013;Huang, Huang, Ouyang, & Qin, 2011;Jing et al, 2016;Ku, Teng, Wang, & Lu, 2009). The present study showed that KB cells can grow at incubation temperatures of 15 and 32°C, but 27°C was the optimum incubation temperature.…”
Section: Discussionmentioning
confidence: 99%
“…KB cells are well adapted to growth at 27°C in L-15 supplemented with 10% FBS without CO 2 . Many cell lines derived from fish are known to grow best between 25 and 30°C (Goswami, Sharma, Bahuguna, Nagpure, & Lakra, 2013;Huang, Huang, Ouyang, & Qin, 2011;Jing et al, 2016;Ku, Teng, Wang, & Lu, 2009). The present study showed that KB cells can grow at incubation temperatures of 15 and 32°C, but 27°C was the optimum incubation temperature.…”
Section: Discussionmentioning
confidence: 99%
“…C . auratus (known as crucian carp) has been cultured in China for several hundred years (Jing et al 2016), and recently played an important role in the international fish trade with a total output of 2,912,258 tons in 2015 (Jia et al 2016). A .…”
Section: Introductionmentioning
confidence: 99%
“…As CyHV-2 mainly affects goldfish, development of species-specific cell line will greatly aid in disease health management. Several cell lines have been employed for isolation of CyHV-2 (Rougée et al, 2007;Yan, Nie & Lu, 2011;Ito et al, 2013;Ma et al, 2015;Jing et al, 2016). In India, Sahoo et al (2016) isolated CyHV-2 using a koi carp cell line, CCKF but could not propagate the virus beyond 4th passage.…”
Section: Discussionmentioning
confidence: 99%